Plant–Microbe Interactions for Improving Postharvest Shelf Life and Quality of Fresh Produce Through Protective Mechanisms - Wajid Zaman; Adnan Amin; Atif Ali Khan Khalil; Muhammad Saeed Akhtar; Sajid Ali (Horticulturae)
Postharvest spoilage of horticultural produce is a significant challenge, contributing to substantial food waste and economic losses. Traditional preservation methods, such as chemical preservatives and fungicides, are increasingly being replaced by sustainable, chemical-free alternatives. Microbial interventions using beneficial bacteria, fungi, and yeasts have emerged as effective solutions to enhance the postharvest quality and extend shelf life. Advancements in omics technologies, such as metabolomics, transcriptomics, and microbiomics, have provided deeper insights into plant–microbe interactions, facilitating more targeted and effective microbial treatments. The integration of artificial intelligence (AI) and machine learning further supports the selection of optimal microbial strains tailored to specific crops and storage conditions, further enhancing the treatment efficacy. Additionally, the integration of smart cold storage systems and real-time microbial monitoring through sensor technologies offers innovative approaches to optimize microbial interventions during storage and transport. This review examines the mechanisms through which microbes enhance the postharvest quality, the role of omics technologies in improving microbial treatments, and the challenges associated with variability and regulatory approval. Amid growing consumer demand for organic and sustainable solutions, microbial-based postharvest preservation offers a promising, eco-friendly alternative to conventional chemical treatments, ensuring safer, longer-lasting produce while reducing food waste and environmental impact.